(untitled) (Archives of Mechanics - Test, 2022)
Molecular dynamics simulations were conducted with the Stillinger–Weber potential at room temperature to study the mechanical properties and find the mode-I critical stress intensity factor of buckled two-dimensional (2D) hexagonal silicon mono-sulfide (SiS) and germanium selenide (GeSe) sheets. Uniaxial tensile tests were simulated for pristine and pre-cracked sheets. 2D Young’s modulus of SiS and GeSe are estimated at 38.3 and 26.0 N/m, respectively. Their 2D fracture strength is about 3.1–3.5 N/m. By using the initial crack length with the corresponding fracture stress, their mode-I critical stress intensity factor is estimated in the range from 0.19 through 0.22 MPa √m. These values differ within 5% from those obtained by the surface energy and are very small compared to the reported fracture toughness of single-crystalline monolayer graphene.